(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research seeks to clarify the problems related to the aspects of the financial and accounting process resulting from entering into contractual arrangements with a period of more than 20 years, among which is the research problem represented by the lack of clarity of the foundations and procedures for the recognition of oil costs and additional costs borne by foreign invested companies, which led to a weakening of their credibility and reflection. Negatively "on the measurement and accounting disclosure of financial reports prepared by oil companies, and the research aims to lay down sound procedures for measuring and classifying oil costs and additional costs paid to foreign companies, and recognizing and recording them in the financial records of these companies through adopting international accounting standards IAS and IFRS, and the importance of Research with the direction of the Republic of Iraq towards adopting these standards starting from 2021 AD, which requires preparing the Iraqi environment from now to accommodate this adoption, and the researcher reached a set of conclusions, the most prominent of which is that the financial statements of the oil companies did not provide adequate and adequate disclosure of the joint contractual arrangements that had a clear impact In the result of corporate activity and its position Financial, and the main reason is the Iraqi oil companies ’failure to adopt international accounting and financial reporting standards. Accordingly, the researcher recommends a set of recommendations, the most important of which is the adoption of all oil companies, including the company, the research sample, international accounting standards IAS and IFRS standards, especially the accounting treatment of the costs of joint contractual arrangements in accordance with the requirements of IFRS11 “Joint Arrangements” and International Accounting Standard IAS28 “Investments in companies. Associates and joint ventures, "to ensure proper accounting measurement and disclosure of the joint contractual arrangements in the financial statements of these companies.